The Implementation of Process Approach to Teaching Writing at the Ninth Grade of SMPN 1 Pelaihari Academic Year 2015/2016 - Supiani, Supiani -- (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
The main objectives of the research are to know the strategy that is used in the process approach to teaching writing, to know the process approach in the implementation of teaching writing at the class, and to find out the implications of the process approach for students learning writing at the ninth grade of SMPN 1 Pelaihari. The research is employed in descriptive qualitative research. The subject of the research is an English teacher and 30 of ninth grade students of the SMP Negeri 1 Pelaihari in the Academic Year of 2015/2016. This research is done at the classroom where the process approach of teaching writing happens at the class. The process approach to teaching writing could improve the students’ writing ability because it engages the pedagogical procedures to the writing process. Through this approach, the students could state main ideas of the topic, then express or organize their ideas dealing with a descriptive text such as identification and description in written form. Moreover, the students were able to minimize grammatical errors especially in the use of simple present tense. In addition, the process approach also could improve the students’ motivation and create good atmosphere at the classroom. They were more actively in asking to the teacher about their problems of writing. When they got difficulty to find the new vocabulary or did not know the structure of sentence, they were more confident to ask for to the teacher individually or through discussing in pair. Keywords: Process Approach, teaching writing, learning process